Parole, parole boards and the institutional dilemmas of contemporary prison release - Guiney, Thomas C. (Punishment & society, 2023)
The decision to release is a defining feature of the carceral experience: at once a necessary function of a dynamic penal system, and a highly contested form of symbolic communication where the anxieties and contradictions of contemporary penality begin to coalesce. In this paper I argue that the institutions we rely upon to make these determinations in a fair, consistent and efficient manner are under increasing strain. Drawing upon insights from historical institutionalism, I seek to show that the parole board model of discretionary decision-making that first emerged during the highwater mark of mid-twentieth century penal modernism has proved remarkably resilient to reform, but is slowly fracturing into a more complex, multi-layered prison release landscape. I explore the implications of this gradual historical transformation and conclude this paper with a call for new ways of thinking about prison release as an increasingly interconnected sphere of penal governance.